Socio-economic and health status of slum dwellers of the Kalyanpur slum in Dhaka city - Latif, Mahmuda Binte; Irin, Anjuman; Ferdaus, Jannatul (Bangladesh Journal of Scientific Research, 2016)
This research was carried out to examine the socio-economic and health condition of slum dwellers of Kalyanpur slum area. The study was both qualitative and quantitative type. In quantitative approach, primary data were used and collected from randomly selected (68 respondents) slum dwellers in the Kalyanpur slum area. The secondary data were collected from journal papers, articles, books, official documents, thesis papers, daily newspapers etc. By analyzing the survey, it is seen that slum dwellers were deprived of basic needs. The study helps to identify the slum problems such as food and housing problems, poor sanitation condition, poor quality or no sewerage and drainage, inadequate educational facilities, lack of utility services like gas facility, electricity connection, piped water supply etc. From this study it is observed that every family live in a slum in unhygienic environment in poor condition. The slum dwellers work as garments workers (24.2%), household workers (13.7%), rickshaw pullers (19.2%), street hawkers, day labourers, masons etc. The range of household income of slum dwellers was about Tk 6,000 - 10,000 and they spent most of their money on food (61.39% of income). It was also seen that most of the slum dwellers were affected by various kinds of seasonal and waterborne diseases like fever, asthma, skin diseases, diarrheoa, jaundice etc. The study finds that poor socio-economic status and inadequacy of urban services has had an immediate effect on urban health specially the slum poor in metropolitan cities in the country. Bangladesh J. Sci. Res. 29(1): 73-83, June-2016